Iphone 13 Pro Max Intellectual Property Rights Legal Protection - Vahleza, Nanda Aza; Nugraha, Tashya Panji; Fairuzzaman, Fahmi (West Science Law and Human Rights, 2025)
This study's goal is to investigate how the iPhone 13 Pro Max's intellectual property rights are protected. The secondary data type being used in this study is primary and secondary legal resources, and one form of data collection is library studies. The methodology employed in this study is a normative juridical approach. The data analysis method is based on qualitative methods to generate descriptive-analytical information. Article 40 paragraph (1) letter f and s, Article 59 paragraph (1) letter e of the Copyright Law, Article 3 paragraph (1) of the Patent Law, Article 1 Number 1 of the Industrial Design Law, Article 1 Number 1 and Article 2 paragraph (3) of the Trademark Law, and Article 1 Numbers 1 and 2 of the Layout Designs of Integrated Circuits all provide some protection for the findings of the study on the legal protection of intellectual property rights pertaining to the iPhone 13 Pro Max.